Copper-catalyzed direct monofluoroalkenylation of C(sp3)–H bonds via decarboxylation of α-fluoroacrylic acids. Issue 17 (27th July 2022) - Lu, Xiao-Yu; Chen, Xing-Ke; Gao, Meng-Ting; Sun, Xiao-Mei; Jiang, Run-Chuang; Wang, Jun-Chao; Yu, Li-Juan; Ge, Meng-Yuan; Wei, Zheng-Huan; Liu, Zi
Abstract : Herein, a protocol for the copper-catalyzed direct monofluoroalkenylation of C(sp 3 )–H bonds is reported. Abstract : Herein, a protocol for the copper-catalyzed direct monofluoroalkenylation of C(sp 3 )–H bonds is reported. A wide range of α-fluoroacrylic acids and C–H patterns were suitable reaction substrates, delivering the corresponding monofluoroalkenes with excellent Z -stereoselectivity. These are vital structural motifs in synthetic organic chemistry and pharmaceutical sciences. In addition to α-fluoroacrylic acids, β-fluoroacrylic acids were also compatible reaction substrates.